2020
DOI: 10.1016/j.jcot.2020.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of idiopathically elevated ESR and CRP in patients undergoing primary total knee arthroplasty as a function of body mass index

Abstract: Background: Erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) are commonly used inflammatory markers utilized to aid in the diagnosis of periprosthetic infection (PJI). Patients with obesity, however, are known to have elevated baseline levels of these inflammatory markers. Therefore, this retrospective study aimed to determine the relationship between elevated ESR and CRP and body mass index (BMI) in patients undergoing total knee arthroplasty (TKA). In doing so, physicians can better determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
3
1
0
Order By: Relevance
“…A publication by Watson, et al looked specifically at idiopathically elevated CRP and ESR in patients undergoing primary TKA. They found that higher BMI was correlated with higher levels of preoperative CRP and ESR [33]. Our study supports this same finding; patients with BMI in the obese category (> 30), were more likely to have elevated preoperative CRP level (OR 4.2, p < 0.0001).…”
Section: Discussionsupporting
confidence: 89%
“…A publication by Watson, et al looked specifically at idiopathically elevated CRP and ESR in patients undergoing primary TKA. They found that higher BMI was correlated with higher levels of preoperative CRP and ESR [33]. Our study supports this same finding; patients with BMI in the obese category (> 30), were more likely to have elevated preoperative CRP level (OR 4.2, p < 0.0001).…”
Section: Discussionsupporting
confidence: 89%
“…Although elevation of ESR or CRP in patients without clinical signs and symptoms of infection is considered an idiopathic elevation, recent studies suggest significant associations between the patients’ characteristics and elevation of inflammatory markers such as ESR and CRP. In this respect, elevated levels of ESR and CRP have been shown to be more prevalent in patients with higher BMI 19. Similarly, the mean BMI of the patients was significantly more in patients with idiopathic ESR elevation in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…In this respect, elevated levels of ESR and CRP have been shown to be more prevalent in patients with higher BMI. 19 Similarly, the mean BMI of the patients was significantly more in patients with idiopathic ESR elevation in the present study. These observations do not support the routine evaluation of ESR as part of the preoperative planning for elective TKA, as obesity is prevalent in patients who are TKA candidates.…”
Section: Discussionsupporting
confidence: 70%
“…This association held true regardless of other associated risk factors, such as smoking, obesity, and diabetes [87]. Contrastingly, in another study involving a sample of 351 patients undergoing their first knee implantation by a single surgeon, no statistically significant difference was found between the risk of PJI and preoperative CRP and ESR levels [88]. One reason for this heterogeneity might be that ESR and CRP can be elevated in various conditions, while multiple factors are considered as predisposing the development of PJI independent of inflammation index values.…”
Section: Preoperatively Elevated Serum Inflammatory Markersmentioning
confidence: 96%